The Role of E-Commerce, Digital Payment, and Accounting Information Systems in Entrepreneurial Decision-Making - Yobel Alvares; Yudea; Ika Makherta Sutadji (Cita konsultindo, 2026)
This study examines the effects of E-Commerce, Digital Payment, and Accounting Information Systems on entrepreneurial decision-making among Accounting students at Universitas Balikpapan. The study is motivated by the rapid acceleration of digital transformation, which has changed business models and created broader entrepreneurial opportunities for young people. However, previous empirical studies have reported inconsistent findings regarding the influence of digital commerce, digital payment systems, and accounting information systems on entrepreneurial decision-making, indicating the existence of an empirical research gap. This study employs a quantitative research design using primary data collected through questionnaires distributed to Accounting students from the 2022–2023 cohorts. The effective sample consists of 86 respondents, selected using the census (total sampling) technique. The hypotheses are tested using multiple linear regression analysis with IBM SPSS version 26. The empirical findings reveal that E-Commerce and Digital Payment do not significantly influence entrepreneurial decision-making, whereas the Accounting Information System has a positive and significant effect. Simultaneously, all three independent variables significantly influence entrepreneurial decision-making, with an explanatory power of 34.4%. These findings provide updated empirical evidence regarding the determinants of entrepreneurial decision-making among university students and contribute to the development of the Technology Acceptance Model (TAM) in explaining technology adoption within entrepreneurial contexts.